Cucurbitaceae endémicas del Perú - León, Blanca (2006)
The Cucurbitaceae are represented in Peru by around 27 genera and 110 species (Brako & Zarucchi, 1993; Ulloa Ulloa et al., 2004), all of them vines and lianas. Here we recognize 23 endemic species in seven genera. One genus, Guraniopsis, is endemic to Peru. Endemic species are found in several regions, as Subtropical Costal Desert and Desert Shrubland, between 150 and 2400 m elevation. We applied IUCN categories and criteria to 10 species. None of the species have been registered within Peru’s protected areas system.